2007
DOI: 10.1089/vbz.2007.0121
|View full text |Cite
|
Sign up to set email alerts
|

Detection of“Rickettsia amblyommii”in Association with a Tick Bite Rash

Abstract: In the summer of 2006, an Amblyomma americanum tick was removed from a woman in central North Carolina, who subsequently developed a rash at the site of tick attachment. When examined by polymerase chain reaction (PCR) for Borrelia, Anaplasma, Ehrlichia, Babesia, Rickettsia, and Bartonella DNA, only the Rickettsia primers generated an amplicon, which was identified as "R. amblyommii" by sequencing. To our knowledge, this is the first case in which R. amblyommii was temporally associated with a rash.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 10 publications
1
55
0
2
Order By: Relevance
“…15 However, a North Carolina woman did develop rash at the site of the bite from an R. amblyommii-positive tick. 16 Similarly, in this study, we observed a sample with strong reactivity to R. amblyommii as confirmed by IFA and western blotting obtained from a patient who did not have fever but experienced rash and the development of an eschar. In comparison with R. rickettsii infection, where fever, headache, and rash are common, infection with R. amblyommii does not necessarily lead to the development of fever and the occurrence of rash is less likely.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…15 However, a North Carolina woman did develop rash at the site of the bite from an R. amblyommii-positive tick. 16 Similarly, in this study, we observed a sample with strong reactivity to R. amblyommii as confirmed by IFA and western blotting obtained from a patient who did not have fever but experienced rash and the development of an eschar. In comparison with R. rickettsii infection, where fever, headache, and rash are common, infection with R. amblyommii does not necessarily lead to the development of fever and the occurrence of rash is less likely.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, R. amblyommii was detected in a tick that subsequently caused rash at the bite site in a patient, although no other symptoms developed. 16 Furthermore, tick surveys conducted in Tennessee have not detected R. rickettsii but R. amblyommii, R. parkeri, and R. montanensis were commonly found. 5,10 Similarly, tick surveys conducted in neighboring states in the southeastern region revealed the same pattern of the predominance of R. amblyommii in Amblyomma americanum ticks, the most ubiquitous and aggressive tick species in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007 it was temporally associated with a macular rash when it was detected in an A. americanum removed from a patient. 30 More recently, a group in North Carolina obtained serum samples from patients considered probable cases of RMSF and found that some of the patients had higher end-point titers against R. amblyommii antigen than R. rickettsii . 11 In our study, the most common rickettsial species in all sexes and stages of ticks was R. amblyommii .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology is still being investigated. One report suggested that R. amblyommii could be the cause of STARI, but the description of the rash did not seem consistent with EM; no photograph was included, and only one case was presented [35]. A Georgia study [12] reported EM rashes on two persons bitten by lone star ticks positive for R. amblyommii, but this does not preclude the rashes being caused by another agent.…”
Section: Discussionmentioning
confidence: 99%